Analysis of the Age Limit for Regional Head Candidates in Supreme Court Decision Number 23P / HUM / 2024 Perspective of Gustav Radbruch's Legal Certainty Theory - Nurrahmah, Fitriyah Nurrahmah; Rukmono, Indra; Dores, Dedi; Prayitna, Reza Dipta (International Journal of Sustainable Law, 2024)
The Supreme Court through decision number 23P/HUM/2024 gave birth to a new provision regarding the age limit of regional head candidates calculated at the inauguration stage, not at the time of determining the candidate pair. This provision has caused polemics among the public because if it is calculated from the inauguration how the KPU and the organizers have difficulty verifying the qualifications of the minimum age limit of the regional head candidates and whether it fulfills the aspects of legal certainty when viewed from the ideas of Gustav Radbruch. This research uses normative research with a case approach model. Gustav Radbruch interpreted legal certainty with 4 indicators, namely (1) law is a positive thing (legislation); (2) law is based on facts; (3) legal facts must be formulated in a clear way (avoiding misinterpretation and easy to implement); and (4) positive law is not easily changed. Supreme Court Decision Number 23P/HUM/2024 when examined from the four indicators initiated by Gustav Radbruch shows legal uncertainty.